2017
DOI: 10.1136/vr.103871
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and outcome of dogs treated medically or surgically for thoracolumbar intervertebral disc protrusion

Abstract: To date, few studies have investigated the clinical characteristics of thoracolumbar intervertebral disc protrusion (IVDP). The aim of this retrospective study was to evaluate the presentation and outcome of dogs receiving medical or surgical treatment for thoracolumbar IVDP. Eighty-four dogs were included, with a median age of 9.4 years. German shepherd dogs and Staffordshire bull terriers were the most common breeds. Significantly more surgically treated dogs (n=53) had neurological deficits and were non-amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Although successful outcomes have been reported after both medical and surgical management of cervical compressive HNPE, it is currently unclear which type of treatment is associated with more favourable outcomes 5 11 13 . Previous studies have suggested that medical management in dogs with spinal disease is usually reserved for dogs with less severe clinical signs and less severe spinal cord compression 8 19–21 . More severe spinal cord compression observed on MRI has indeed been considered the most important indicator to elect surgery over medical treatment in dogs with cervical compressive HNPE 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Although successful outcomes have been reported after both medical and surgical management of cervical compressive HNPE, it is currently unclear which type of treatment is associated with more favourable outcomes 5 11 13 . Previous studies have suggested that medical management in dogs with spinal disease is usually reserved for dogs with less severe clinical signs and less severe spinal cord compression 8 19–21 . More severe spinal cord compression observed on MRI has indeed been considered the most important indicator to elect surgery over medical treatment in dogs with cervical compressive HNPE 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs tend to reflect the chronic, slowly progressive nature of the IVD degeneration, typically with milder neurological deficits than those seen with acute spinal cord injury secondary to IVD extrusions ( 63 ). The characteristic clinical picture is therefore that of a slowly progressive, often non-painful myelopathy in an older, usually non-chondrodystrophic dog ( 63 , 64 ). Pain can be present depending on the presence of nerve root compression but is less common than in the more acute IVD extrusion.…”
Section: Types Of Intervertebral Disc Herniationmentioning
confidence: 99%
“…Diagnosis is made with advanced imaging . Conservative management (anti‐inflammatory drugs, rest combined with rehabilitation) is more appropriate in dogs with mild deficits and with less severe spinal cord compression, with a success rate of 29% and mean survival time of 330 days . Surgical management is indicated in dogs with more severe deficits and progressive signs, with a success rate of 71% and mean survival time of 630 days .…”
Section: Introductionmentioning
confidence: 99%
“…Conservative management (anti‐inflammatory drugs, rest combined with rehabilitation) is more appropriate in dogs with mild deficits and with less severe spinal cord compression, with a success rate of 29% and mean survival time of 330 days . Surgical management is indicated in dogs with more severe deficits and progressive signs, with a success rate of 71% and mean survival time of 630 days . Various surgical techniques have been described (hemilaminectomy with anulectomy, minihemilaminectomy with partial lateral corpectomy, dorsal laminectomy, partial lateral corpectomy, hemilaminectomy with vertebral stabilization, hemilaminectomy with partial discectomy), with associated immediate postoperative clinical deterioration reported particularly in approaches to the lamina and pedicle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation